Experimental evidence that evolutionary relatedness does not affect the ecological mechanisms of coexistence in freshwater green algae. (23rd September 2013) - Narwani, Anita; Alexandrou, Markos A.; Oakley, Todd H.; Carroll, Ian T.; Cardinale, Bradley J.; De, Luc
Abstract The coexistence of competing species depends on the balance between their fitness differences, which determine their competitive inequalities, and their niche differences, which stabilise their competitive interactions. Darwin proposed that evolution causes species' niches to diverge, but the influence of evolution on relative fitness differences, and the importance of both niche and fitness differences in determining coexistence have not yet been studied together. We tested whether the phylogenetic distances between species of green freshwater algae determined their abilities to coexist in a microcosm experiment. We found that niche differences were more important in explaining coexistence than relative fitness differences, and that phylogenetic distance had no effect on either coexistence or on the sizes of niche and fitness differences. These results were corroborated by an analysis of the frequency of the co‐occurrence of 325 pairwise combinations of algal taxa in > 1100 lakes across North America. Phylogenetic distance may not explain the coexistence of freshwater green algae.